Influenza Virus Types, Subtypes and Genomic Lineage with Its Prevention and Control: A Narrative Review - Mahmud, Shahriar; Tamanna, Rumana Kaniz (Journal of Monno Medical College, 2024)
Since influenza viruses continue to be a serious hazard to both humans and animals, they are still very important. Types A, B, and C influenza viruses are among the members of the Orthomyxoviridae family. A quick summary of the molecular factors is provided, which determine pathogenicity and clinical signs and symptoms of influenza. A review of host range and evolution highlights the genetic diversity of influenza A viruses and their capacity to successfully infect a variety of hosts, including avian and mammalian species. Moreover, influenza viruses may reassemble segments because of the way their segmented genome is designed. The significance of host sialic acid distribution and viral receptor-binding hemagglutinins in species-restricted virus binding is emphasized. It results in yearly outbreaks and necessitates the creation of novel vaccination formulations. This may ultimately result in the creation of a virus that can spread among humans and has unique antigenic qualities, perhaps sparking a pandemic. Current developments in our knowledge of the seasonality, transmission, and prevention of influenza viruses are outlined, along with their significance for halting the virus's spread. Journal of Monno Medical College June, 2024; 10 (1):43-51